2011
DOI: 10.1200/jco.2010.33.7808
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Postchemotherapy Azoospermia With Microsurgical Testicular Sperm Extraction: The Weill Cornell Experience

Abstract: To our knowledge, this represents the largest series of postchemotherapy microdissection TESE-ICSI to date. Sperm were retrieved in 37% of patients despite a prevalence of Sertoli cell-only pattern on preoperative biopsy. Although prechemotherapy sperm cryopreservation is recommended, treatment with microdissection TESE and ICSI are effective treatment options for many azoospermic men after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 17 publications
3
68
0
2
Order By: Relevance
“…Even in men persistently azoospermic after cancer treatment, including ablative chemotherapy, testicular spermatozoa may be recovered for ICSI. 67 Lastly, in adult azoospermic 47,XXY Klinefelter patients, spermatozoa can be recovered for ICSI. 68,69 Apart from a multiple biopsy approach, the most important factor to improve sperm recovery from testicular specimens is the microscopic assessment of the wet preparation and the concomitant application of erythrocyte-lysing buffer and/or enzymatic digestion.…”
Section: Azoospermia and Icsimentioning
confidence: 99%
“…Even in men persistently azoospermic after cancer treatment, including ablative chemotherapy, testicular spermatozoa may be recovered for ICSI. 67 Lastly, in adult azoospermic 47,XXY Klinefelter patients, spermatozoa can be recovered for ICSI. 68,69 Apart from a multiple biopsy approach, the most important factor to improve sperm recovery from testicular specimens is the microscopic assessment of the wet preparation and the concomitant application of erythrocyte-lysing buffer and/or enzymatic digestion.…”
Section: Azoospermia and Icsimentioning
confidence: 99%
“…If a patient is unable to produce a sample, alternative sources of sperm include microsurgical epididymal aspiration, electroejaculation, or testicular biopsy. New methods for in vitro fertilization (IVF) include intrauterine insemination (IUI) and intracytoplasmic sperm injection (ICSI), and these methods have improved fertility outcomes for men with low sperm counts or motility defects [28,32].…”
Section: Currently Available Fertility-preserving Methods For Malesmentioning
confidence: 99%
“…In the largest case series to date, Schlegel et al 22 document their experience of mTESE in 73 men with persistent post-chemotherapy azoospermia, with a mean interval post-treatment of 19.9 years. During this study, Sertoli-cell only pattern histology was observed in the majority of patients, which is consistent with previous studies on testicular function following chemotherapy 11,19,34 .…”
Section: Post-chemotherapy Azoospermia and Mtesementioning
confidence: 99%
“…Therefore, surgical sperm retrieval is implicated as a potential means of allowing men with cancer to have a realistic chance of fathering a biological child. Of these surgical techniques, microdissection testicular sperm extraction (mTESE) balances the greatest likelihood of successful sperm retrieval with an acceptable profile of adverse affects 22 . However, barriers and questions still remain before this specialised technique can form part of routine practice.…”
Section: Introductionmentioning
confidence: 99%